PENGARUH INTERAKSI STRATEGI DAN SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL - Muslichah Muslichah (Akutansi Bisnis & Manajemen ( ABM ), 2003)
This study investigated the interaction effect of strategy and management accounting systems (MAS) on managerial performance. MAS was defined in term of perceived availability of two characteristics of information, which were scope and timeliness. To assess the interaction effect, data were collected from 57 managers of manufacturing industry by way of mail surveys combined with personal contact. The results of this study indicated that strategy and the availability of MAS characteristics of broad scope and timeliness were associated with higher managerial performance.